Destroying Yemen : What Chaos in Arabia Tells Us about the World - Blumi, Isa, 1969- (Book collections on Project MUSE., 2018)
"Since March 2015, a Saudi-led international coalition of forces--supported by Britain and the United States--has waged devastating war in Yemen. Largely ignored by the world's media, the resulting humanitarian disaster and full-scale famine threatens millions. Destroying Yemen offers the first in-depth historical account of the transnational origins of this war, placing it in the illuminating context of Yemen's relationship with major powers since the Cold War. Bringing new sources and a deep understanding to bear on Yemen's profound, unwitting imbrication in international affairs, this explosive book ultimately tells an even larger shock-doctrine story of today's political economy of global capitalism, development, and the war on terror as disparate actors intersect in Arabia."--Provided by publisher.